Treino sem consequências diferenciais: importância conceitual, metodológica e algumas implicações educacionais - BAPTISTA, Marcelo Quintino Galvão (2013)
In this article we review the principal findings from a series of studies about conditional discrimination training without differential consequences, which have been conducted in our laboratory with human participants who had no previous experience as research subjects. We seek to describe the procedures utilized and discuss the results obtained with reference to conceptual and methodological aspects which these studies share in common. In particular, we focus on reinforcement (in terms of its temporal schedule), and alternative sources of control (Sample-Sc and Sample-Si matching, as well as reexposure to the training trials). Finally, we draw a relationship between the procedural routine and the role of teachers in the classroom, and suggest some educational implications which may be involved in the programming and implementation of instructional strategies.